Myopia progression in children and adolescents: impact of COVID-19 pandemic and current and future control strategies - Kassem, Ahmed (Acta Biomedica Atenei Parmensis, 2023)
Abstract: Myopia is a significant and growing public health problem with typical onset or progression during childhood adolescence. High myopia has lifelong impact on ocular health and socio-economic aspects of patients ‘lives. COVID-19 lockdown resulted in demonstrable increase in incidence and progression rate of myopia in children and adolescence. Low dose atropine and Orthokeratology contact lenses appear to be most effective in slowing down myopia progression. Rebound progression after stopping both modalities were reported. Defocus modifying spectacle lenses and contact lenses are less effective but possibly better tolerated.